Ironing out the cross talk between FGF23 and inflammation - David, Valentin (Am J Physiol Renal Physiol, 2016)
The bone-secreted hormone fibroblast growth factor 23 (FGF23) has an essential role in phosphate homeostasis by regulating expression of the kidney proximal tubule sodium-phosphate cotransporters as well as parathyroid hormone levels. Induction of FGF23 early in chronic kidney disease (CKD) helps to maintain normal phosphorous levels. However, high FGF23 levels become pathological as kidney disease progresses and are associated with an increased risk of CKD progression, cardiovascular events, and death. The factors responsible for increasing FGF23 levels early in CKD are unknown, but recent work has proposed a role for inflammation and disordered iron homeostasis. Notably, FGF23 has recently been shown to elicit an inflammatory response and to display immunomodulatory properties. Here, we will review emerging evidence on the cross talk between inflammation, iron, FGF23, and bone and mineral metabolism and discuss the relevance for CKD patients.